Analysis of agricultural production instability in the Gezira scheme - Mohamed Elamin Abd Ellatif Mahir; Hag Hamad Abdelaziz (Journal of the Saudi Society of Agricultural Sciences)
The study was conducted to measure the extent of instability and contribution of different components to change in mean production of the main crops grown in the Gezira scheme. The study used time series data covering the period before the adoption of liberalization policy (1970/71 to 1991/92) and the period after the adoption of liberalization policy (1992/93 to 2007/08). The main crops included in the study were sorghum, wheat, cotton and groundnuts. The instability of area, yield and production were determined, in addition to the analysis of different components of the sources of change in the mean production of crops. The findings of the study showed that sorghum, wheat and cotton witnessed a continuous increase in instability over the two periods, whereas there was a decrease in the instability of groundnuts production during post-liberalization period. The instability in area and yield of all crops moved in the same direction and their increasing/decreasing trend resulted in increase/decrease in instability. The decomposition analysis of sources of change in mean production of crops indicated that changes in mean yield accounted for large shares of the change in mean production of wheat and sorghum but change in mean area contributed largely in cotton and groundnuts. Furthermore, the analysis showed that changes in the variance of yield accounted for large share of changes in the variance of production for sorghum, while for wheat the large share was due to variance of area. The changes in the residual term were important in explaining the changes in the variance of production in the case of groundnuts. Programs and policies such as rehabilitation of irrigation canals, provision of inputs and strengthening the agricultural research and extension can play a vital role in achieving stability in the agricultural production in the Gezira scheme.